2011
DOI: 10.1002/jssc.201100336
|View full text |Cite
|
Sign up to set email alerts
|

New method for determination of (E)‐resveratrol in wine based on microextraction using packed sorbent and ultra‐performance liquid chromatography

Abstract: An ultra-fast and improved analytical methodology based on microextraction by packed sorbent (MEPS) combined with ultra-performance LC (UPLC) was developed and validated for determination of (E)-resveratrol in wines. Important factors affecting the performance of MEPS such as the type of sorbent material (C2, C8, C18, SIL, and M1), number of extraction cycles, and sample volume were studied. The optimal conditions of MEPS extraction were obtained using C8 sorbent and small sample volumes (50-250 mL) in one ext… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

1
31
0

Year Published

2012
2012
2020
2020

Publication Types

Select...
8

Relationship

3
5

Authors

Journals

citations
Cited by 51 publications
(32 citation statements)
references
References 43 publications
1
31
0
Order By: Relevance
“…In recent years, the ability of several extraction techniques, such as solid-liquid extraction (SLE) [19], enzyme-assisted extraction [20], heat extraction [21], solid-phase extraction (SPE) [22], and solid-phase microextraction (SPME) [23], for the isolation free low molecular-weight polyphenols (LMW-PPs) from vegetables and other food matrices, has been proposed and evaluated as reliable alternatives to classic liquid-liquid extraction (LLE) technique. More recently, a novel analytical approach, based on miniaturized microextraction by packed sorbent (MEPS), followed by ultrahigh pressure liquid chromatography (UHPLC) separation, has been proposed by Gonç alves et al [24] for quantitative determination of wine biologically active phenolic constituents and trans-resveratrol [25]. In the last few years, a quick, easy, cheap, effective, rugged and safe (QuEChERS) extraction technique for the multiclass, multiresidue analysis of pesticides in fruits and vegetables, was described by Anastassiades et al [26].…”
Section: Introductionmentioning
confidence: 99%
“…In recent years, the ability of several extraction techniques, such as solid-liquid extraction (SLE) [19], enzyme-assisted extraction [20], heat extraction [21], solid-phase extraction (SPE) [22], and solid-phase microextraction (SPME) [23], for the isolation free low molecular-weight polyphenols (LMW-PPs) from vegetables and other food matrices, has been proposed and evaluated as reliable alternatives to classic liquid-liquid extraction (LLE) technique. More recently, a novel analytical approach, based on miniaturized microextraction by packed sorbent (MEPS), followed by ultrahigh pressure liquid chromatography (UHPLC) separation, has been proposed by Gonç alves et al [24] for quantitative determination of wine biologically active phenolic constituents and trans-resveratrol [25]. In the last few years, a quick, easy, cheap, effective, rugged and safe (QuEChERS) extraction technique for the multiclass, multiresidue analysis of pesticides in fruits and vegetables, was described by Anastassiades et al [26].…”
Section: Introductionmentioning
confidence: 99%
“…Selection of sorbent is an important factor to achieve acceptable clean-up and get high extraction yield [30]. Therefore the performance of the five MEPS sorbent materials: C2 (ethyl-silica), C8 (octyl-silica), C18 (octadecyl-silica), SIL (unmodified silica) and M1 (a mixed mode sorbent containing 80% C8 and 20% strong cationic exchange (SCX)) was tested and compared, in order to select the best sorbent for the target analytes.…”
Section: Optimization Of the Factors Affecting The Performance Of Mepsmentioning
confidence: 99%
“…In this context the microextraction by packed sorbent (MEPS) appears as a new format for solid-phase extraction (SPE) that has been miniaturized to work with sample volumes as small as 10 L [29,30]. The commercially available presentation of MEPS uses the same sorbents as conventional SPE columns and so is suitable for use with most existing methods by scaling the reagent and sample volumes.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…The best source of resveratrol in food is considered to be red wine. The average recommended dose of red wine is 2 glasses (approximately 300 mL, which is a conservative estimate), and it has been recently reported that some red wines may contain as much as 40-50 mg resveratrol per litre (Gonçalves and Camara 2011). This would equate to a dose of as much as 15 mg resveratrol in 300 mL of wine, which is slightly lower than that used to improve cardiac structure and function in animal models of ischemic heart disease and hypertension in 2 above-mentioned studies (Chan et al 2011;Lin et al 2008).…”
mentioning
confidence: 99%